Incidence of Augmentation in Primary Restless Legs Syndrome Patients May Not Be That High: Evidence From A Systematic Review and Meta-Analysis. Issue 2 (January 2016) - Liu, Guang Jian; Wu, Lang; Wang, Song Lin; Ding, Li; Xu, Li Li; Wang, Yun Fu; Chang, Li Ying
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Augmentation is a common complication of primary restless legs syndrome (RLS) during treatment; however, its incidence rate remains unclear. The aim of this study is investigate the rate of augmentation during RLS treatment. We searched 6 databases, including PubMed, OVID, Embase, Wiley citations, Web of Science research platform (including SciELO Citation Index, Medline, KCI Korean Journal Database, the Web of Science™ Core Collection), and the Cochrane library, and screened the reference lists of the included trials and recently published reviews. Randomized controlled trials and observational studies that reported augmentation events during RLS treatment. Primary RLS patients older than 18 years. No restrictions regarding intervention types were applied. Three investigators independently extracted and pooled the data to analyze the augmentation rate of the total sample and of patient subgroups with different interventions, treatment durations and drug regimens and different geographic origins. Fixed-effects or random-effects model was used for pooled analysis. A total of 60 studies involving 11, 543 participants suggested an overall augmentation rate of 5.6% (95% confidence intervals (CI), 4.0–7.7). The augmentation incidence was 6.1% (95% CI, 4.1–9.1) for long-term treatment and 3.3% (95% CI, 1.4–7.3) for short-term treatment. In addition, 27.1% (95% CI, 12.3–49.5) of the levodopa-treated patients, 6.0% (95% CI, 4.1–8.8) of the patients treated with dopamine agonists, and 0.9% (95% CI, 0.2–3.3) of the patients taking pregabalin or gabapentin developed augmentation. Augmentation occurred in 7.2% (95% CI, 5.0–10.3) of the patients taking immediate-release drugs and in 1.7% (95% CI, 0.6–5.0) of the patients taking transdermal application. The main limitations are that the augmentation rates were not evaluated according to drug dosage, gender, and age and symptom severity. Approximately 5 to 6 in 100 RLS patients developed augmentation during treatment.